Assessing the biopotency of the rAAV9 vector In Vitro - Pratikshya Adhikari; Peter G. Nichols; Stephen M. Vorobiov; Tierra A. Bobo; Haiyan Fu (PLoS ONE, 2026)
The potency assay is critical to ensure the effectiveness and consistency of recombinant Adeno-associated Virus (AAV) gene therapy vectors, especially clinical-grade products. AAV serotype 9 (AAV9), known for its neurotropic properties and ability to cross the blood-brain barrier, has been a favored vector for targeting neurogenetic diseases. However, assessing AAV9 biopotency has been challenging due to the insusceptibility of the commonly used cell lines to AAV9. To address this, we utilized a cell-based potency assay using the liver-derived human hepatoma (HuH-7) cell line to evaluate infection by self-complementary (sc)-AAV9 vector expressing human N-sulfoglucosamine sulfohydrolase (hSGSH), currently undergoing evaluation as a potential treatment for Mucopolysaccharidosis (MPS) IIIA. The potency of various scAAV9-h SGSH vector batches was tested in HuH-7 cells which reproducibly expressed the transgene, resulting in measurable SGSH production. The SGSH expression and vector genome copies of various vector batches correlated linearly with the viral vector dose (R 2 = 0.71–0.95), indicating a generally strong correlation. The reproducibility of the assay was demonstrated by consistent vector copy numbers and SGSH activity in transduced cells across multiple independent runs. Statistical analysis of the results showed high reliability, with relative intra-assay consistency showing a coefficient of variation (CV) of less than 20%) and inter-assay reproducibility with a CV of less than 25%) affirming the precision of the test. Additionally, our data also demonstrate that long-term (>2.5 years) storage at 2–4°C had no impact on the biopotency of rAAV9 vector confirming long-term stability of the vectors. Hence, we have effectively assessed the biopotency of rAAV9 vector in vitro utilizing HuH-7 cells. Overall, this in vitro assay provides a practical and reliable method to assess AAV9 potency, offering a valuable alternative to animal models and supporting the functional quality and consistency of AAV9 gene therapy vector products in general.